VACINAÇÃO ANTI-RÁBICA EM BOVINOS: COMPARAÇÃO DE CINCO ESQUEMAS VACINAIS - Albas, A. (2022)
The Brazilian Program for Rabies Control indicates the use of 2 doses of a vaccine with inactivated virus. This study was conducted to determine the best schedule for cattle vaccination. To evaluate this, 45 bovines were organized in 5 groups (9 animals each), identified as A, B, C, D and E. Group A received only the dose at day 0; groups B and C received one booster at days 30 and 180, respectively; groups D and E received two boosters, delivered at days 30 and 60 and 30 and 180, respectively. Blood samples were withdrawn at days 0 (negative control), 30, 60, 90, 180, 210 and 360 after the beginning of vaccination. Specific antibody levels were determined in sera samples by the rapid fluorescent focus inhibition test (RFFIT). Samples showing titers ? 0.5 IU/mL were considered positive. Group E, whose protocol included two boosters, was the most efficient because it induced high and persistent specific antibody levels. The results reinforce the need of booster application in rabies vaccination to keep the prophylactic efficacy of inactivated vaccines. In view of these results the authors suggest the use of 3 doses of a vaccine with inactivated virus: one priming dose followed by two boosters delivered at days 30 and 180 after the initial dose.